Improving the Growth and Productivity of Barley through Genotypes and Sowing Time Scheduling in Sub-tropical Humid Climate: Sowing Time Effects on Barley in Sub-tropical Humid Climate - Kharub, Ajit Singh; Ram, Hari; Singh, Bhagat; Yadav, Malu Ram; Singh, SB; Kumar, Neeraj; Chander, Subhash; Singh, Gyanendra (Journal of Cereal Research, 2025)
The researchers are compelled to modify their previous strategies and look into new alternative crop establishing practices due to the increasing pressure that climate change is placing on the agricultural productivity. The goal of the current study is to determine how sowing timing and variety affect the growth and production of the barley crop. The multi-locational experiment was conducted in split plot design with four dates of sowing (26th October-5th November, 6-15th November, 16-25th November and 26th November - 5th December) in main plots and two barley varieties (BH946 and DWRB160) in sub-plots on a sandy loam and loamy-sand soils at multi-locations (Karnal, Agra, Durgapura, Hisar and Ludhiana) during Rabi seasons of 2020-21 and 2021-22. According to the study's findings, the maximum tillers per square metre, dry matter accumulation, grains per spike, and grain and straw yield occurred for crop sown between 6 November and 15 November, and these values were significantly greater than those for other sowing dates. The six-row barley variety BH946 with more grains per spike and straw production had the best grain yield of all the kinds. In the north-western plain zone (NWPZ), a one-month delay in sowing time (from the last week of October to the last week of Nov) resulted in a yield penalty of 11.2-40.7%. In order to increase the production of the barley crop, the optimum sowing time as well as crop variety are crucial. This was demonstrated by the considerable interaction between sowing time and variety.